Prognostic Impact of PCK1 Protein Kinase Activity-Dependent Nuclear SREBP1 Activation in Non-Small-Cell Lung Carcinoma - Shao, Fei; Bian, Xueli; Wang, Juhong; Xu, Daqian; Guo, Wei; Jiang, Hongfei; Zhao, Gaoxiang; Zhu, Lei; Wang, Shuai; Xing, Dongming; Gao, Yibo; He, Jie; et al. (Frontiers in Oncology, 2021)
Metabolic enzymes can perform non-metabolic functions and play critical roles in the regulation of a variety of important cellular activities. Phosphoenolpyruvate carboxykinase 1 (PCK1), a gluconeogenesis enzyme, was recently identified as an AKT-regulated protein kinase that phosphorylates INSIG1/2 to promote nuclear SREBP1-dependent lipogenesis. However, the relationship of this regulation with the progression of non-small-cell lung carcinoma (NSCLC) is unclear. Here, we demonstrate that the expression levels of AKT pS473, AKT-dependent PCK1 pS90, PCK1-mediated INSIG1 pS207/INSIG2 pS151, and nuclear SREBP1 were higher in the 451 analysed human NSCLC specimens than in their adjacent normal tissues, and the expression levels of these proteins were positively correlated with each other in tumour specimens. In addition, the expression levels of PCK1 pS90, INSIG1 pS207/INSIG2 pS151, and nuclear SREBP1 were associated with TNM stage and progression in NSCLC. Importantly, levels of PCK1 pS90 or INSIG1 pS207/INSIG2 pS151 were positively correlated with poor prognosis in NSCLC patients, and the combined expression values of PCK1 pS90 or INSIG1 pS207/INSIG2 pS151 had a better prognostic value than that of each individual protein expression value and was an independent prognostic marker for NSCLC. These findings reveal the role of PCK1-mediated nuclear SREBP1 activation in NSCLC progression and highlight the potential to target the protein kinase activity of PCK1 for the diagnosis and treatment of human NSCLC.